THE EFFECT OF INTEGRATED USE OF DISEASE IN MANAGAMENT INTERVENTIONS IN ASTHMA AND COPD : A TEN YEARS SYSTEMATIC REVIEW - Sijabat , Landong; Novettiandari, Guinanti (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Asthma and COPD affect an estimated 64 million and 235 million people respectively, worldwide. Obstructive lung disease evaluation and therapy was based on severity and in accordance with current asthma and COPD treatment guidelines. The aim: The aim of this study to show about the effect of integrated use of disease in management interventions in asthma and COPD. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: IDM is defined as “a group of coherent interventions, designed to prevent or manage 1 or more chronic conditions using a community wide, systematic and structured multidisciplinary approach potentially employing multiple treatment modalities”. IDM typically has several components, such as self-management education, skills training, care management, and structured follow-up.